2021
DOI: 10.3390/foods10092217
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Antimicrobial Properties of Mediterranean Wild Edible Plants: We Still Know Too Little about Them, but What We Do Know Makes Persistent Investigation Worthwhile

Abstract: (1) Introduction: Bacterial resistance to antibiotics is estimated to be the cause of a major number of deaths by 2050 if we do not find strategies to slow down the rise of drug resistance. Reviews on Mediterranean wild edible plants (MWEPs) with antimicrobial properties are scarce in the main databases (PubMed, Scopus, and WoS). Hence, we proceeded to conduct a new review of the studies on MWEPs. (2) Methods: We used ‘wild edible plant’ and ‘antimicrobial’ as keywords. Within this group, exclusion criteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…A similar trend was observed by Siroli et al [41], who indicated that marinated pork meat presented a lower altering microbial load compared to unmarinated samples, from the sixth to the thirteenth day of storage. Several studies have highlighted the broad spectrum of antimicrobial effect of Mediterranean species against a high number of microorganisms [47][48][49], which has been established and extended in the present work. The same trend was observed by Osaili et al [10], who studied the antimicrobial effect of plant extracts (EOs or specific compounds) on spoilage microorganisms in marinated and vacuum-packed camel meat during storage at 4 and 10 • C. Similarly, Haute et al [50] studied the effect of thyme EOs and specific compounds on the shelf life of marinated fish and meat, concluding that this method constitutes a potential tool to curb spoilage microorganisms.…”
Section: Microbiological Analysis Of Rabbit Meatmentioning
confidence: 77%
“…A similar trend was observed by Siroli et al [41], who indicated that marinated pork meat presented a lower altering microbial load compared to unmarinated samples, from the sixth to the thirteenth day of storage. Several studies have highlighted the broad spectrum of antimicrobial effect of Mediterranean species against a high number of microorganisms [47][48][49], which has been established and extended in the present work. The same trend was observed by Osaili et al [10], who studied the antimicrobial effect of plant extracts (EOs or specific compounds) on spoilage microorganisms in marinated and vacuum-packed camel meat during storage at 4 and 10 • C. Similarly, Haute et al [50] studied the effect of thyme EOs and specific compounds on the shelf life of marinated fish and meat, concluding that this method constitutes a potential tool to curb spoilage microorganisms.…”
Section: Microbiological Analysis Of Rabbit Meatmentioning
confidence: 77%